First, subtract color(red)(8x) from each side of the equation to put the equation in standard quadratic form:
8x - color(red)(8x) = x^2 - color(red)(8x) - 9
0 = x^2 - 8x - 9
x^2 - 8x - 9 = 0
We can now use the quadratic equation to solve this problem:
The quadratic formula states:
For color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0, the values of x which are the solutions to the equation are given by:
x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))
Substituting:
color(red)(1) for color(red)(a)
color(blue)(-8) for color(blue)(b)
color(green)(-9) for color(green)(c) gives:
x = (-color(blue)(-8) +- sqrt(color(blue)(-8)^2 - (4 * color(red)(1) * color(green)(-9))))/(2 * color(red)(1))
x = (8 +- sqrt(64 - (-36)))/2
x = (8 +- sqrt(64 + 36))/2
x = (8 - sqrt(100))/2; x = (8 + sqrt(100))/2
x = (8 - 10)/2; x = (8 + 10)/2
x =(-2)/2; x = 18/2
x =-1; x = 9
The Solution Set Is:
x ={-1, 9}